Effects of compound microbial inoculant treated wastewater irrigation on soil nutrients and enzyme activities - Chunfang, Wang; Xiaohou, Shao; Huilian, Xu; Tingting, Chang; Weina, Wang (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Wastewater treated by compound microbial inoculant (CMI) in agricultural irrigation can enrich soil fertility and decompose the possible pollutants. In this study, a greenhouse experiment using tomato as the model crop was performed to investigate the effects of treated wastewater irrigation on soil nutrients and enzymes. For this purpose, certain parameters were measured, including soil total nitrogen (N), nitrate N, total phosphorus (P), available potassium (K) and the activities of the enzymes urease, acid phosphatase and catalase in soils irrigated with fresh water, wastewater and CMI-treated wastewater under three amount of irrigation water. The results showed that irrigation with both treated and untreated wastewater significantly increased soil total N, total P, and available K, however the treated wastewater showed higher effects on soil enrichment, especially on available K. The activity of soil urease and acid phosphatase reached highest with treated wastewater irrigation, whereas wastewater irrigation increased the activity of catalase obviously. Soil enzyme and nutrient with fresh water irrigation decreased with increasing water amount; the content of soil urease, nitrate-nitrogen, total N and total P in treated wastewater and wastewater irrigation rose with increasing water amount, but the highest activity of acid phosphatase and the lowest activity of catalase were found in medium irrigation water amount. Under the condition of tomato cultivation, total N, nitrate N and total P were closely correlated with soil urease and catalase; there were significant positive correlation among soil urease, catalase, total N, nitrate N and total P; there existed significantly positive correlation between acid phosphatase and all measured soil nutrient indexes. The results suggested that irrigation with CMI-treated wastewater is a security and effective strategy to agricultural land management. Keywords: wastewater irrigation, water quality, soil enzyme activity, soil nutrients, compound microbial inoculant (CMI) DOI: 10.3965/j.ijabe.20160906.2127 Citation: Wang C F, Shao X H, Xu H L, Chang T T, Wang W N. Effects of compound microbial inoculant treated wastewater irrigation on soil nutrients and enzyme activities. Int J Agric & Biol Eng, 2016; 9(6): 100－108.